Specificity of accounting operations for the construction of townhouses - Rubtsova О. (Ways to Improve Construction Efficiency, 2018)
In the article features of accounting of new objects of investment in the real estate market of Ukraine - town houses are considered. The solution of the task of reflecting the accounting in the process of construction of these objects in the accounts of accounting and the formation of their value is proposed.